Glutaminase-Deficient Mice Display Hippocampal Hypoactivity, Insensitivity to Pro-Psychotic Drugs and Potentiated Latent Inhibition: Relevance to Schizophrenia - Gaisler-Salomon, Inna (2009)
Dysregulated glutamatergic neurotransmission has been strongly implicated in the pathophysiology of schizophrenia (SCZ). Recently, presynaptic modulation of glutamate transmission has been shown to have therapeutic promise. We asked whether genetic knockdown of glutaminase (gene GLS1) to reduce glutamatergic transmission presynaptically by slowing the recycling of glutamine to glutamate, would produce a phenotype relevant to SCZ and its treatment. GLS1 heterozygous (GLS1 het) mice showed about a 50% global reduction in glutaminase activity, and a modest reduction in glutamate levels in brain regions relevant to SCZ pathophysiology, but displayed neither general behavioral abnormalities nor SCZ-associated phenotypes. Functional imaging, measuring regional cerebral blood volume, showed hippocampal hypometabolism mainly in the CA1 subregion and subiculum, the inverse of recent clinical imaging findings in prodromal and SCZ patients. GLS1 het mice were less sensitive to the behavioral stimulating effects of amphetamine, showed a reduction in amphetamine-induced striatal dopamine release and in ketamine-induced frontal cortical activation, suggesting that GLS1 het mice are resistant to the effects of these pro-psychotic challenges. Moreover, GLS1 het mice showed clozapine-like potentiation of latent inhibition, suggesting that reduction in glutaminase has antipsychotic-like properties. These observations provide further support for the pivotal role of altered glutamatergic synaptic transmission in the pathophysiology of SCZ, and suggest that presynaptic modulation of the glutamine–glutamate pathway through glutaminase inhibition may provide a new direction for the pharmacotherapy of SCZ.